The Big Book of Letterheads - Edited by Carter, David E. (New York Collins Design : Distributed throughout the world by Harper Collins Publishers, 2007)
Although email has overtaken written communication in business, letterhead design is just as vital as ever. Since business letters are mailed less frequently, each one sent has the opportunity to have a greater impact on the reader that it would have in the pre-internet era. Today's designers are challenged to create a letterhead (and letterhead set) that will accomplish the following: make a positive first impression for the business; be an appropriate design for the firm's personality and corporate culture; and leave a lasting impression in the mind of the recipient. In addition, the "letterhead set" will usually contain an envelope-one which ideally says "open me first." THE BIG BOOK OF LETTERHEADS includes nearly 400 letterhead sets, all selected for their ability to inspire the reader and provide countless brainstorming ideas.
Include Illustrations and Index.
Keywords: Commercial art -- Letterheads